Modelling of ECG signals with applications to telemedicine and diagnosis of cardiac arrhythmias - Ge, Ding Fei. (2008)
In this project, Autoregressive (AR) modeling is used to model the normal and abnormal ECG signals for compression, decompression and diagnosis.